Papaya Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
This document provides comprehensive information on growing papaya in Florida's home landscapes. It covers the scientific name, common names, origin, and distribution of papaya. Detailed descriptions of tree types, leaves, flowers, and fruit are included. The article also discusses climate requirements, propagation methods, crop yields, spacing, pruning, soil types, planting techniques, care practices, pest and disease management, and the nutritional value of papaya fruit. Practical advice on site selection, irrigation, mulching, and harvesting is provided to ensure successful papaya cultivation. Publication date: 1986.